2021
DOI: 10.1063/5.0021350
|View full text |Cite
|
Sign up to set email alerts
|

Superconductivity in type-II Weyl-semimetal WTe2 induced by a normal metal contact

Abstract: WT e 2 is a material with rich topological properties: it is a 2D topological insulator as a monolayer and a Weyl-semimetal and higher-order topological insulator in a bulk form. Inducing superconductivity in topological materials is a way to obtain topological superconductivity, which lays at the foundation for many proposals of fault tolerant quantum computing. Here, we demonstrate the emergence of superconductivity at the interface between WTe2 and the normal metal palladium. The superconductivity has a cri… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
4

Relationship

3
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 51 publications
2
21
0
Order By: Relevance
“…The observation of superconductivity in our samples is an interesting phenomenon on its own and it requires a separate study [17]. Our WTe 2 crystals are not intrinsically superconducting.…”
Section: Superconductivity Induced In Wte 2 By Normal Leadsmentioning
confidence: 84%
“…The observation of superconductivity in our samples is an interesting phenomenon on its own and it requires a separate study [17]. Our WTe 2 crystals are not intrinsically superconducting.…”
Section: Superconductivity Induced In Wte 2 By Normal Leadsmentioning
confidence: 84%
“…The van-der-Waals (vdW) material WTe 2 is predicted to be a higher-order TI [11][12][13][14][15], hosting topological edge states at its crystal hinges. It was recently shown that thin crystals of the material placed on top of palladium (Pd) bottom contacts turn superconducting [16], with a pronounced flow of super-current along the edges of a Josephson junction (JJ) formed out of this material system [17].…”
Section: Introductionmentioning
confidence: 99%
“…Another characteristic feature of WTe 2 is the extreme positive transverse magnetoresistance MR ⊥ , which can reach values as high as 10 5 % for magnetic fields ∼9 T applied parallel to the c−axis of bulk or thin flakes of WTe 2 in the Fermi liquid phase at T ∼ 100 mK [40][41][42]. In addition, evidence of topologically protected conducting edge states [43] and flat-band superconductivity in close proximity to Pd [44] and Nb [45] was shown in bulk and few layers WTe 2 flakes, while quantum spin Hall states are found in mechanically exfoliated monolayer WTe 2 [46]. Most of the reported literature on T d -WTe 2 concerns bulk crystals or mechanically exfoliated flakes.…”
Section: Introductionmentioning
confidence: 99%